2009
DOI: 10.1007/s00467-009-1229-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and management of isolated moderate renal pelvis dilatation detected at postnatal screening

Abstract: The aim of this study was to evaluate the incidence and outcome of isolated moderate renal pelvis dilatation (RPD) [anterior-posterior diameter (APD) 10-15 mm] in an unselected population of 2-month-old infants prospectively followed for up to 12-14 months of life. Isolated moderate renal pelvis dilatation was detected in 282 of the 11,801 (2.4%), infants screened; 240 infants with normal renal ultrasound were enrolled as the control group. Resolution of RPD was considered when an APD Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
4
25
1
Order By: Relevance
“…Our study found that there was no significant relationship between age or gender and bacteriuria or funguria, perhaps because boys were more likely develop UPJO, [5,6] whereas girls were much more likely to develop a UTI after 1 year [9]. Increasingly, UPJO is discovered by prenatal ultrasound [6], but being diagnosed by prenatal ultrasound was not a risk factor to develop bacteriuria or funguria.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Our study found that there was no significant relationship between age or gender and bacteriuria or funguria, perhaps because boys were more likely develop UPJO, [5,6] whereas girls were much more likely to develop a UTI after 1 year [9]. Increasingly, UPJO is discovered by prenatal ultrasound [6], but being diagnosed by prenatal ultrasound was not a risk factor to develop bacteriuria or funguria.…”
Section: Discussioncontrasting
confidence: 60%
“…UPJO is common in children, for which Anderson-Hynes pyeloplasty is the classic surgical treatment [5,6] < B1 B2 > < /C< B3 B4 > <, and there have been some reports concerning about UTI in patients with UPJO [1,2]. Unlike previous studies, in the present study, urine taken directly from the renal pelvis was cultured.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In recent years, the number of papers analyzing the significance of mild isolated antenatal hydronephrosis has been increasing. Even though almost all authors agree that unilateral mild isolated hydronephrosis is a benign condition [1,2,8,9], there have been a few studies reporting on the clinical significance and the outcome of newborns (NBs) with bilateral mild isolated hydronephrosis [9][10][11]. NBs with bilateral hydronephrosis, especially male NBs, are considered to be a group with a higher risk of having a significant abnormality and/or impairment of postnatal renal function [12].…”
Section: Introductionmentioning
confidence: 99%